2019
DOI: 10.1021/acs.jnatprod.9b00403
|View full text |Cite
|
Sign up to set email alerts
|

Myxochelin- and Pseudochelin-Derived Lipoxygenase Inhibitors from a Genetically Engineered Myxococcus xanthus Strain

Abstract: Precursor-directed biosynthesis was used to introduce selected aryl carboxylic acids into the pseudochelin pathway, which had recently been assembled in Myxococcus xanthus. Overall, 14 previously undescribed analogues of the natural products myxochelin B and pseudochelin A were generated and structurally characterized. A subset of 10 derivatives together with their parental molecules were evaluated for their activity toward human 5-lipoxygenase. This testing revealed pseudochelin A as the most potent 5lipoxyge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…The NADPH-dependent reductase domain of MxcG releases an aldehyde intermediate from the assembly line by reduction of the thioester, which is further reduced by MxcG to form myxochelin A or transaminated by MxcL to form myxochelin B [ 10 , 11 ]. Although it has been shown that the promiscuity of MxcE allows the activation and loading of other benzoic acid derivatives to the assembly line to form precursor-derived non-natural myxochelin derivatives [ 12 , 13 , 14 ], the incorporation of heteroaromatic carboxylic acid precursors has so far not been described.…”
Section: Introductionmentioning
confidence: 99%
“…The NADPH-dependent reductase domain of MxcG releases an aldehyde intermediate from the assembly line by reduction of the thioester, which is further reduced by MxcG to form myxochelin A or transaminated by MxcL to form myxochelin B [ 10 , 11 ]. Although it has been shown that the promiscuity of MxcE allows the activation and loading of other benzoic acid derivatives to the assembly line to form precursor-derived non-natural myxochelin derivatives [ 12 , 13 , 14 ], the incorporation of heteroaromatic carboxylic acid precursors has so far not been described.…”
Section: Introductionmentioning
confidence: 99%
“… Chemical structure of myxochelin A (R 1 =OH) and B (R 1 =NH 2 ) ( 4 ). While the two catechol moieties can be varied by precursor‐directed biosynthesis, the core region is amenable to combinatorial biosynthesis [85–87] …”
Section: Engineering Anti‐inflammatory Natural Productsmentioning
confidence: 99%
“…Late‐stage functionalization is thus likely the most promising alternative for modifications on the myxochelin core. Eventually, the two bioengineering strategies were combined to generate 5‐LOX inhibitors that are equipotent to the FDA‐approved drug zileuton [87] …”
Section: Engineering Anti‐inflammatory Natural Productsmentioning
confidence: 99%
See 2 more Smart Citations